THE PHYSICAL SPATIAL DEVELOPMENT OF TIAKUR CITY, MOA ISLAND, MALUKU PROVINCE, INDONESIA - Heinrich Rakuasa; Reinhard Nolly Limba; Stewart Pertuack; Arda Fadhli Romadhon; Raihan Rabbani (Yayasan Nuraini Ibrahim Mandiri, 2026)
Tiakur City, the capital of Maluku Barat Daya Regency, has undergone significant physical development between 2015 and 2025, driven by population growth and economic activities. This study employs a quantitative approach using remote sensing technology with PlanetScope satellite imagery to analyze land cover changes. The analysis reveals an increase in built-up land area from 171.29 hectares (7.31%) in 2015 to 395.66 hectares (16.89%) in 2025, while non-built-up land experienced a decline. These findings indicate a rapid development rate and highlight the importance of sustainable spatial planning. In conclusion, understanding the patterns and intensity of land cover changes in Tiakur City is crucial for evaluating spatial planning policies and improving infrastructure development planning for the future